KELAYAKAN DAN RESPON PENGGUNA TERHADAP VIDEO FOTOSINTESIS BAGI SISWA SMP - Rafina Rafina; Maulid Nadian Putrini; Dyah Pramesthi Isyana Ardyati (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
The limitations of visualization and low student learning motivation due to the lack of innovative media facilities in the abstract material of plant photosynthesis are the background of this research. This problem triggers the failure of seventh grade junior high school students in building a complete mental representation of the biochemical processes of plants. The main focus of this research is to evaluate the level of feasibility of photosynthesis learning videos for students and analyze teacher and student responses to the acceptance of this technology. The method applied is the research and development method (R&D) with a limited feasibility test design. Actual data collection was collected using expert validation sheets, a four-level Likert scale questionnaire, and open-ended questions, which were then analyzed using quantitative percentage techniques and thematic analysis. Quantitative data from expert assessments revealed that this video met the criteria of very suitable in the media aspect at 95.8 percent, the material aspect at 92.5 percent, and the category of suitable in the language aspect with an achievement of 75.0 percent. Furthermore, the analysis of user responses resulted in an average score of very good usefulness from teachers of 3.8 and positive appreciation from students reaching 85.0 percent. The main conclusion confirms that the tested photosynthesis learning video product is highly suitable as a supporting instrument to facilitate concrete cognitive needs. This digital media is recommended as an adaptive strategy to ensure the sustainable success of the high school science learning transformation agenda. ABSTRAK Keterbatasan visualisasi serta rendahnya motivasi belajar peserta didik akibat minimnya fasilitas media inovatif pada materi abstrak fotosintesis tanaman melatarbelakangi penelitian ini. Masalah tersebut memicu adanya kegagalan siswa kelas VII SMP dalam membangun representasi mental yang utuh mengenai proses biokimia tumbuhan. Fokus utama penelitian ini adalah mengevaluasi tingkat kelayakan video pembelajaran fotosintesis bagi siswa serta menganalisis respon guru dan siswa terhadap penerimaan teknologi tersebut. Metode yang diterapkan yaitu metode penelitian pengembangan (Research and Development) dengan desain uji kelayakan terbatas. Pengumpulan data aktual dikumpulkan menggunakan lembar validasi ahli, angket kuesioner skala Likert empat tingkat, dan pertanyaan terbuka, yang selanjutnya dianalisis melalui teknik persentase kuantitatif serta analisis tematik. Data kuantitatif hasil penilaian para ahli menyingkap bahwa video ini memenuhi kriteria sangat layak pada aspek media sebesar 95,8 persen, aspek materi senilai 92,5 persen, serta kategori layak pada aspek bahasa dengan capaian 75,0 persen. Lebih lanjut, analisis respon pengguna menghasilkan skor rata-rata kemanfaatan yang sangat baik dari guru sebesar 3,8 dan apresiasi positif siswa mencapai 85,0 persen. Simpulan utama menegaskan bahwa produk video pembelajaran fotosintesis teruji sangat layak sebagai instrumen pendukung dalam memfasilitasi kebutuhan kognitif secara konkret. Media digital ini direkomendasikan sebagai strategi adaptif untuk menyukseskan agenda transformasi pembelajaran sains sekolah menengah secara berkelanjutan.